2012
DOI: 10.2485/jhtb.21.237
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Immunohistochemical Study of the Characteristics of Dental Follicle

Abstract: The purpose of this study was to examine the histopathological and immunohistochemical characteristics of the dental follicle (DF) attached to impacted tooth. A total of 38 cases of DF diagnosed histopathologically between 2000 and 2011 at the Department of Oral Pathology, Nihon University School of Dentistry, Matsudo City, Japan were used in the study. Among the 38 cases, 10 cases which did not undergo decalcification were selected for immunohistochemistry. Histologically, the DF was composed of inner and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Most of the ectomesenchymal cells showed negative expression of CD34, but focal positivity at the periphery just below the surface epithelium. Scattered CD34 positive ectomesenchymal cells have been reported in the inner layer of dental follicle indicating the ectomesenchymal component of POT shares cellular characteristics and origin with dental follicle.…”
Section: Discussionmentioning
confidence: 92%
“…Most of the ectomesenchymal cells showed negative expression of CD34, but focal positivity at the periphery just below the surface epithelium. Scattered CD34 positive ectomesenchymal cells have been reported in the inner layer of dental follicle indicating the ectomesenchymal component of POT shares cellular characteristics and origin with dental follicle.…”
Section: Discussionmentioning
confidence: 92%
“…showed that the outer and inner layers, especially the lat- reported that mesenchymal cells in the inner layer were positive for vimentin and α-smooth muscle actin (12) .…”
Section: Histological Examination Of the Hdf On Hande Stainingmentioning
confidence: 99%